PENGARUH EFIKASI DIRI DALAM UPAYA PENINGKATAN KINERJA MELALUI KEPUASAN KERJA PADA PT. ABADI JAYA RANTAUPRAPAT - Zebua, Yuniman (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
This study aims to determine self-efficacy in an effort to improve performance through job satisfaction at PT. Abadi Jaya Rantauprapat either partially or simultaneously and with a single test. The number of samples was determined using a census with the same number as the population, namely 59 people. The method used is multiple linear regression analysis and hypothesis testing. From the partial hypothesis testing (t test), the results show that self-efficacy has a positive and significant effect on performance improvement with tcount (3.196) t table (1.672) with a significant value of 0.002 <0.05; Job satisfaction has a positive and significant effect with tcount (3.339)> t table (1.672) with a significant value of 0.000 <0.05; The test results by mediating self-efficacy and increased performance through job satisfaction have a positive and significant effect with a value of 2.853> 1.98 or 5%; The test results simultaneously self-efficacy and job satisfaction have a positive and significant effect on performance improvement with Fcount (34.001)> Ftable (3.16) with a significant 0.000an <0.05; Performance improvement can be explained by self-efficacy and job satisfaction by 53.2% while the remaining 46.8% can be explained by factors not examined in this study.